World naval aviation - Beaver, Paul (Jane's Information Group, 1989)
This reference work examines developments in naval and maritime aviation around the world. The focus is on identifying the embarked and land-based assets used in 88 countries with coastlines to protect and economic interests to safeguard. Each country's entry details the organizations flying, naval or maritime aircraft, with information on command structures, air-capable ships, shore bases, recent operations, typical deployments as well as the assets available and the weapon systems they carry.